Understanding Eco-Anxiety as a mediator between emotional stability and Eco-Activism - Widyayanti, Yorri Violeta; Mustika, Martina Dwi (International Journal of Research in Counseling and Education, 2023)
Current climate change demands concrete behavior that has a positive impact on the environment, namely eco-activism. Eco-activism is influenced by various factors, one of which is emotional stability. The emergence of eco-activism can also be caused by a person’s eco-anxiety. This study aims to present an overview of the correlations between eco-activism, emotional stability, and eco-anxiety in Indonesian society, where eco-anxiety has a role as a mediator. On-line questionnaires comprising the Ten Item Personality Inventory (TIPI), the Hogg Eco-Anxiety Scale (HEAS-13) and the Pro-Environmental Behavior Scale (PEBS-2013) were administered to 279 Indonesian citizens (WNI) aged 19–65 years. The results of this study shows that having emotional stability can enable an individual to react to challenging circumstances like climate change in an environmentally beneficial manner. Furthermore, an individual's emotional stability greatly impacts their ability to effectively handle challenging situations, frequently linked with feelings of anxiety. Interestingly, anxiety related to climate change can enhance a person's motivation to positively contribute to environmental efforts.Moreover, eco-anxiety significantly mediates the correlation between emotional stability and eco-activism.This research provides an overview of the relationship between emotional stability, eco-anxiety, and eco-activism in Indonesian society, which has not been widely researched.